2018
DOI: 10.1104/pp.18.00571
|View full text |Cite
|
Sign up to set email alerts
|

BIG Regulates Dynamic Adjustment of Circadian Period in Arabidopsis thaliana

Abstract: Circadian clocks drive rhythms with a period near 24 h, but the molecular basis of the regulation of the period of the circadian clockis poorly understood. We previously demonstrated that metabolites affect the free-running period of the circadian oscillator of Arabidopsis (), with endogenous sugars acting as an accelerator and exogenous nicotinamide acting as a brake. Changes in circadian oscillator period are thought to adjust the timing of biological activities through the process of entrainment, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…The clock, in its role as master regulator, must balance these two competing requirements. Recently it has been proposed that the clock in plants is dynamically plastic, able to respond to changes in environmental inputs by altering phase and period (54,55). A decentralized structure, with organ specific inputs to clocks that are coupled together, could allow some flexibility in sensing the environment whilst ensuring robust timing.…”
Section: Discussionmentioning
confidence: 99%
“…The clock, in its role as master regulator, must balance these two competing requirements. Recently it has been proposed that the clock in plants is dynamically plastic, able to respond to changes in environmental inputs by altering phase and period (54,55). A decentralized structure, with organ specific inputs to clocks that are coupled together, could allow some flexibility in sensing the environment whilst ensuring robust timing.…”
Section: Discussionmentioning
confidence: 99%
“…The clock, in its role as master regulator, must balance the competing requirements of flexibility and robustness. Recently, it has been proposed that the clock in plants is dynamically plastic, able to respond to changes in environmental inputs by altering its period and phase [77,78]. Cell-cell coupling increases the synchrony and robustness of oscillations, influencing how easy it is for clocks to entrain to the environment [79].…”
Section: Discussionmentioning
confidence: 99%
“…How BIG can control PCD mediated by the MIPS1 pathway is difficult to decipher because the molecular function of BIG is still unknown. Indeed, the BIG gene encodes a 5078-aa protein with several functional domains and has been implicated in numerous hormonal and light pathways [19][20][21]25,27,32,36 . One hypothesis could have been that the MI content was restored in the mips1 somi2 double mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Other big mutants were subsequently identified, exhibiting a variety of morphological defects and resistance to the auxin's effect on endocytosis 19,20 ; reduced response to cytokinin, ethylene, and gibberellins 21 ; corymb-like inflorescences 22,23 ; or characterized by mis-regulation of mitochondrial stress signalling 24 . BIG has been also described for its involvement in the circadian clock control 25 and in elevated CO 2 -induced stomatal closure 26 . Recently 27 , demonstrated that BIG represents a new regulator of the Jasmonic Acid (JA) pathway and a point of convergence for the interactions of JA and others hormones.…”
mentioning
confidence: 99%